Men’s hair in post-war Britain: class, masculinity and cultural change, c.1955-1975 - Anderson, Mark Edward (2020)
Between the mid-1950s and the mid-1970s, British men let their hair down. Throughout the first half of the twentieth century the overwhelming majority of British males had worn short hair and, with the exception of the occasional moustache-craze, had been clean-shaven. In the space of a few short years all of this changed, and by the early 1970s long hair, sideburns, moustaches and beards – articles of appearance which had held connotations of delinquency, dirtiness, effeminacy and deviance – were a common sight on high streets across the country. This shift in fashion, highly contested and widely debated by contemporary observers, has yet to be analysed in any depth by historians of post-war Britain. This thesis represents the first critical social and cultural history of white men’s hair in Britain between the mid-1950s and the mid-1970s, providing a detailed examination of changing fashions and the explosion of discourse which surrounded these shifts in style. Drawing upon Alan Sinfield’s concept of ‘the faultline’, it argues that the stories that were told about men’s hair during the immediate post-war decades were inescapably intertwined with understandings, anxieties and hopes for a wider moment of social and cultural flux. Shifts in hair fashions reflected these broader upheavals, but men’s hair – and the surrounding discourse – also helped to shape how individuals understood a post-war society and culture which was changing around them. The thesis considers a series of case studies in order to explore both lived experience, and the discursive significance of men’s hair within British society between the mid-1950s and the mid-1970s: classroom disputes between teenagers, parents and schools over the length and styling of male pupils’ hair; the efforts to exclude long-haired “beatniks” from leisure spaces in English seaside towns; the emergence of a new, heterosexualised ideal of flamboyant “peacock” masculinity; and the rise of the upmarket men’s hairdressing salon during the post-war period. Each of these chapters engages with wider questions of class and gender to make interventions concerning the decline of deference, shifting ideals of masculinity, and the extent and character of post-war cultural change.